Identifying the Maximum Allowable Soil Moisture Depletion to Enhance Cotton Production Irrigated by Multiple Sprinkler Irrigation Technologies - Farzam Moghbel; Jonathan Aguilar (Kansas Agricultural Experiment Station Research Reports, 2025)
Proper irrigation scheduling is one of the critical fundamentals of successful cotton establishment in arid and semi-arid regions. Soil moisture monitoring could be one of the practical methods to schedule irrigations to optimize cotton growth. However, finding a suitable value of soil moisture that can be used as a trigger point for irrigation initiation during the growing season has remained unsolved. In this study, the profitability of cotton production was considered along with a water conservation perspective to identify this trigger point when monitoring soil moisture. Therefore, field experiments were conducted in 2024 to investigate the cotton response to a particular maximum allowable soil moisture depletion, which could protect cotton final production and result in water resources conservation under various irrigation technologies in western Kansas. The research outputs showed that the highest cotton yield (2682.7 lb/a) was detected when applying irrigation, followed by 50% depletion of available soil moisture, regardless of irrigation technologies. However, applying irrigation followed by an 80% depletion of available soil moisture is recommended when the water supply is highly limited. The irrigation that was triggered by 80% soil moisture depletion resulted in a 20% reduction in cotton production compared to 50% soil moisture depletion conditions under all irrigation technologies (bubbler, sprayer, and MDI’s sprayer). In this study, for the first time, the functionality of the sprayers attached to mobile drip irrigation (MDI) laterals was tested for cotton production. These sprayers are connected to the drip lines to be used for germination purposes and in circumstances where laterals cannot be used. In this growing season, the highest cotton production (2252.7 lb/a) was found to utilize these attached sprayers compared to other irrigation technologies. However, a similar cotton yield (2212.4 lb/a) was found using bubblers as target irrigation technology. Overall, the results of this study could be used as a baseline for producers of cotton in western Kansas, especially when their water is limited, and an acceptable cotton yield is needed.
Keywords: cotton; irrigation; MAD; maximum allowable depletion; nozzle; sprinkler